ʻAnusō̜n nư̄ang nai ngān phrarātchathān phlœ̄ng sop Phon ʻĒk Phao Bō̜riphanyutthakit Mō̜.Pō̜.Chō̜., Mō̜.Wō̜.Mō̜., Thō̜.Chō̜.Wō̜. na mēn nā phlapphlā ʻItsariyāphō̜n Wat Thēpsirinthrāwāt, 18 Phrưtsačhikāyon 2513. - Phao Bō̜riphanyutthakit, 1893-1970 (Krung Thēp : Khrō̜pkhrūa Phon ʻĒk Phao Bō̜riphanyutthakit, 1970)
Cremation volume for Phao Bō̜riphanyutthakit, 1893-1970, former Thai general and cabinet ministers in various governments; comprises biography, condolences, and articles on silver and golden ware of Thailand.
Keywords: Phao Bō̜riphanyutthakit, -- 1893-1970 -- Death and burial; Generals -- Thailand -- Biography; Cabinet officers -- Thailand -- Biography; Goldwork -- Thailand; Silverwork -- Thailand